Sex-Dependent Differences in Physical Exercise-Mediated Cognitive Recovery Following Middle Cerebral Artery Occlusion in Aged Rats - Cohan, Charles H.; Youbi, Mehdi; Saul, Isabel; Ruiz, Alex A.; Furones, Concepcion C.; Patel, Pujan; Perez, Edwin; Raval, Ami P.; Dave, Kunjan R.; Zhao, Weizhao; Dong, Chuanhui; Rundek, Tatjana; et al. (Frontiers in Aging Neuroscience, 2019)
Stroke remains a leading cause of death and disability in the United States. No current treatments exist to promote cognitive recovery in survivors of stroke. A previous study from our laboratory determined that an acute bout of forced treadmill exercise was able to promote cognitive recovery in 3 month old male rats after middle cerebral artery occlusion (MCAo). In this study, we tested the hypothesis that six days of intense acute bout of forced treadmill exercise (physical exercise – PE) promotes cognitive recovery in 11-14 month old male rats. We determined that PE was able to ameliorate cognitive deficits as determined by contextual fear conditioning. Additionally, we also tested the hypothesis that PE promotes cognitive recovery in 11-13 month old reproductive senescent female rats. In contrast to males, the same intensity of exercise that decrease cognitive deficits in males was not able to promote cognitive recovery in female rats. Additionally, we determined that exercise did not lessen infarct volume in both male and female rats. There are many factors that contribute to higher stroke mortality and morbidities in women and thus, future studies will investigate the effects of PE in aged female rats to identify sex differences.